BARRIERS ASSOCIATED WITH INACCESSIBLE MENTAL HEALTH SERVICES FOR YOUTH REFUGEES AND ASYLUM SEEKERS: AN INTEGRATIVE REVIEW - Barbo, Geneveave; Petrucka, Pammla (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
Youth refugees and asylum seekers are vulnerable to mental health conditions. Although their mental health needs are well documented, evidence reveals that they are underutilizing mental health services. This integrative literature review aims to examine the evidence on barriers to mental health access experienced by youth refugees and asylum seekers, determine the literature gaps, and identify the future direction of research in the field. Academic databases, such as CINAHL, OVID MEDLINE (R), PsycINFO, EMBASE, and Web of Science, as well as grey literature, were used to identify eligible articles. A total of 29 articles were included in this review. Our findings revealed 5 major themes: (a) approachability and ability to perceive; (b) acceptability and ability to seek; (c) availability, accommodation, and ability to reach; (d) affordability and ability to pay; and (e) appropriateness and ability to engage. These findings can assist multiple stakeholders in improving mental health access, quality, and provision.